Analisis dan Perancangan Sistem Informasi Administrasi Kependudukan Pada Desa Kota Karang - Saputra, Chindra; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2017)
Problems in the administration of the occupation of the village of Kota Karang to the absence of a systemto manage data on population which has a database of mutual terinregrasi as well as reporting sluggish.The purpose of this research was to analyze and design the system of the administration of population onthe population data, employee Administration certificate as well as centralized reporting databsenya. Thisresearch method either using UML (Unified Modeling Language) to design the system. The results of thisresearch resulted in the design of administrative information systems process data directly to theintegrated population making the letters as well as a description of the reporting system. This plan couldbe developed into an application that can be implemented, as well as expected this research can be areference and learning especially in the field of information systems.